2020
DOI: 10.1093/femsec/fiaa252
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification patterns of methanotrophs and their genetic controllers in water columns of oxygen-stratified boreal lakes

Abstract: The vertical structuring of methanotrophic communities and its genetic controllers remain understudied in the water columns of oxygen-stratified lakes. Therefore, we used 16S rRNA gene sequencing to study the vertical stratification patterns of methanotrophs in two boreal lakes, Lake Kuivajärvi and Lake Lovojärvi. Furthermore, metagenomic analyses were performed to assess the genomic characteristics of methanotrophs in Lovojärvi and the previously studied Lake Alinen Mustajärvi. The methanotroph communities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 79 publications
2
49
0
Order By: Relevance
“…The quality assessment of the raw sequence reads, merging of paired end reads, alignment, chimera removal, preclustering, taxonomic classification (and removal of chloroplast, mitochondria, and eukaryote sequences) and division of 16S rRNA gene sequences into operational taxonomic units (OTUs) at 97 % similarity level was conducted as previously described (Rissanen et al 2020). Singleton OTUs (OTUs with only 1 sequence) were removed, and the data were then normalized by subsampling to the same size, 77340 sequences.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality assessment of the raw sequence reads, merging of paired end reads, alignment, chimera removal, preclustering, taxonomic classification (and removal of chloroplast, mitochondria, and eukaryote sequences) and division of 16S rRNA gene sequences into operational taxonomic units (OTUs) at 97 % similarity level was conducted as previously described (Rissanen et al 2020). Singleton OTUs (OTUs with only 1 sequence) were removed, and the data were then normalized by subsampling to the same size, 77340 sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Methylococcales in the study lake) (Fig. S1), include members that harbored genetic potential for denitrification in the hypoxic and anoxic water columns of closely located Lake Alinen-Mustajärvi (within 20 km from the study lake) and Lake Lovojärvi (within 4 km) (Rissanen et al 2018(Rissanen et al , 2020. In addition, Methylobacter in boreal lake sediments have genetic potential for denitrification, as indicated by our functional annotation analysis (Prokka, version 1.14.5, Seemann 2014) finding genes coding for dissimilatory nitrate and nitrite reduction in two MAGs representing genus Methylobacter in sediments of Lake Alinen Mustajärvi (NCBI accession no.…”
Section: Methanotrophic Community In the Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous environmental studies employing stable isotope probing (SIP) or mRNA-based analyses, showed that gammaproteobacterial methanotrophs are predominant and thrive at oxic-anoxic interfaces with rapid oxygen fluctuations (e.g., lake sediments, mangrove sediments, rice paddies, and peatlands; He et al, 2012;Reim et al, 2012;Shiau et al, 2018;Kaupper et al, 2020Kaupper et al, , 2021. For instance, vertical stratification along an oxygen gradient in a stratified lake has been observed, supported by metagenomic analysis revealing the genetic potential for aerobic methane oxidation under micro-oxic conditions, with the gammaproteobacterial methanotrophs (e.g., Methylobacter) present at the oxic-anoxic interface, and alphaproteobacterial methanotrophs present and stratified at the oxic water layer (Blees et al, 2014;Rissanen et al, 2018Rissanen et al, , 2020.…”
Section: Aerobic Methanotrophs Under Micro-oxic Conditionsmentioning
confidence: 98%
“…The majority of lacustrine CH 4 is produced by anaerobic methanogenic archaea as the end product of remineral-S. van Grinsven et al: Methane oxidation in Lake Lovojärvi ization of organic matter in anoxic sediments (Bartlett and Harriss, 1993;Rudd, 1980). From the sediments, CH 4 can diffuse into the water column and may be emitted to the atmosphere at the water-air interface.…”
Section: Introductionmentioning
confidence: 99%